2020
DOI: 10.1108/md-10-2019-1400
|View full text |Cite
|
Sign up to set email alerts
|

Imitation in immigrant entrepreneurship: an analytical framework

Abstract: PurposeThe phenomenon of imitation has attracted immense attention in studies of big companies, but it has been largely neglected in the immigrant entrepreneurship research thus far. The purpose of this paper is to address that gap by proposing a theoretical framework for studying immigrant entrepreneurship imitation decisions.Design/methodology/approachThe framework is based on a review of relevant literature covering the issue of imitation within three perspectives: institutional, heuristics of judgement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Some of the literature refers to migrant entrepreneurship (Berntsen et al, 2021;Hagos, Izak, and Scott, 2019;Sinkovics and Reuber, 2021;Solano, 2021;Szczygiel, Nunes, and Ramos, 2020), while some refers to immigrant entrepreneurship. (Abbasian and Yazdanfar, 2015a;Bolzani and Boari, 2018;Glinka and Hensel, 2020;Murphy, Bogue, and O'Flaherty, 2020;Širec and Tominc, 2017;Yazdanfar and Abbasian, 2013). For this paper, both 'migrant' and 'immigrant' literature are suitable, if the condition of foreign-born is met.…”
Section: Background 21 Definitions Of Migrant Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the literature refers to migrant entrepreneurship (Berntsen et al, 2021;Hagos, Izak, and Scott, 2019;Sinkovics and Reuber, 2021;Solano, 2021;Szczygiel, Nunes, and Ramos, 2020), while some refers to immigrant entrepreneurship. (Abbasian and Yazdanfar, 2015a;Bolzani and Boari, 2018;Glinka and Hensel, 2020;Murphy, Bogue, and O'Flaherty, 2020;Širec and Tominc, 2017;Yazdanfar and Abbasian, 2013). For this paper, both 'migrant' and 'immigrant' literature are suitable, if the condition of foreign-born is met.…”
Section: Background 21 Definitions Of Migrant Entrepreneurshipmentioning
confidence: 99%
“…In a review of the literature on self-employment and entrepreneurship, Szaban and Skrzek-Lubasi nska (2018) position self-employment within the entrepreneurship paradigm. Amongst authors included in our review, definitions of entrepreneur include creating or establishing a business (Glinka and Hensel, 2020;Širec and Tominc, 2017;Solano, 2021), owning a business (Abbasian and Yazdanfar, 2015;Yazdanfar, Abbasian, and Brouder, 2015), managing one's one business (Szczygiel et al, 2020), and having an aim to succeed at business (Hagos et al, 2019). Given that migrants who are just getting started in their host countries and seeking support from government entrepreneurship initiatives may not have established a business yet, the broader definition by Hagos et al, (2019) seems the most comprehensive for this study.…”
Section: Background 21 Definitions Of Migrant Entrepreneurshipmentioning
confidence: 99%
“…Based on a fuzzy set analysis of more than 500 entrepreneurs, the study found three different pathways for entrepreneurial decision-making during crisis: crisis conditions, enterprising operations and focus, and enterprising capabilities. The next paper titled "Imitation in immigrant entrepreneurship: an analytical framework" (Glinka & Hensel, 2020) tackle another timely and prominent issue in the world, that of immigration and entrepreneurship. The paper proposes a theoretical framework for studying immigrant entrepreneurship imitation decisions, which offers 12 propositions and identifies a research agenda for future studies.…”
Section: The Contexts Of Entrepreneurial Decision-making and Behaviourmentioning
confidence: 99%
“…The next paper titled "Imitation in immigrant entrepreneurship: an analytical framework" (Glinka and Hensel, 2020) tackle another timely and prominent issue in the world, that of immigration and entrepreneurship. The paper proposes a theoretical framework for studying immigrant entrepreneurship imitation decisions, which offers 12 propositions and identifies a research agenda for future studies.…”
Section: The Contexts Of Entrepreneurial Decision-making and Behaviourmentioning
confidence: 99%
“…Migrant entrepreneurship has been the subject of research carried both in Poland and abroad, resulting in a growing number of publications (see e.g. Andrejuk, 2017;Brzozowski, 2019;Glinka, 2013Glinka, , 2018Glinka and Hensel, 2020;Glinka and Jelonek, 2020;Wysieńska, 2012).…”
Section: Introductionmentioning
confidence: 99%